Analysis of increased paclitaxel hypersensitivity at a single institution in setting of COVID 19 vaccination. Issue 28 (1st October 2022) - Jain, Nikita; Bhargava, Anika; Weaver, Kelly; Volz, Lesley; Conliffe, Brette; Ingles, Lauren; Dong, Brian
Abstract : 364 Background: Paclitaxel is a commonly used chemotherapy agent effective in various malignancies. It is known to cause serious and potentially life-threatening hypersensitivity reactions (HRs). Pre-medication protocols have been employed, however approximately 10% of patients will still experience these reactions (1). On an internal review at the University of Louisville, Brown Cancer Center (UofL, BCC) there has been a considerable increase in the incidence of paclitaxel HRs from 4.2% in March 2020 - March 2021 to 14.8% in March 2021 - April 2022. Identifying risk factors that may predispose patients to these reactions is an area of interest in an effort to reduce these events. In this study we investigated clinical characteristics between patients that tolerated paclitaxel versus those who had a HR within the last year with a particular focus on the COVID-19 vaccine given the recent pandemic. Methods: This is a single center retrospective case-control study done at the UofL, BCC. Data was collected on patients who received cycle one day one paclitaxel from March 2021 to April 2022 (n = 135), and patients who developed a reaction were identified. Patient characteristics including demographics, COVID vaccination status, and prior allergies were also collected (table). A T-test analysis was performed between the two groups – those who had a HR and those who did not. Results: Of the 135 patients, 20 were found to have a HR. Absolute lymphocyte count (ALC) was found to be significantly higher with an average of 1125 in the HR group versus 853 in the no reaction group (p = 0.0357). Patients in the HR group also had fewer lines of chemotherapy with an average of 1.15 versus the no reaction group of 1.4 (p = 0.039). There was no significant difference between patients who received the COVID-19 vaccine and those who did not (table). Conclusions: Patients who experienced paclitaxel HRs were found to have higher levels of ALC and tend to be earlier in their treatment course with having undergone fewer lines of chemotherapy. Of note COVID-19 vaccination status appears to have no association with those experiencing paclitaxel HRs. The clinical implications of this requires further exploration in future studiesStatistical analysis of patient characteristics between those who experienced a paclitaxel HR versus those who did not. Characteristics Paclitaxel Reaction (n = 20) No Reaction (n = 113) P Value Age, mean 62.1 63.4 0.589 Stage, mean 3.15 2.94 0.381 Sex Male 4 23 0.957 Female 16 89 Lines of Treatment, mean 1.15 1.4 0.039 COVID-19 Vaccine Received Yes 14 83 0.719 No 6 29 # COVID Vaccine Doses, mean 2.36 2.49 0.53 WBC, mean 8.14 8.01 0.881 ANC, mean 6310 4589 0.053 ALC, mean 1125 853 0.0357 AEC, mean 140 79 0.203 Prior Allergies Yes 11 64 0.863 No 9 48 Days from 1st Vaccine to Paclitaxel, mean 173 241.5 0.118 References Weiss RB, et al. Hypersensitivity Reactions to the Taxanes Paclitaxel and Docetaxel. J of Clin Oncol . 1990; 8(7):1263-8.